Increased Choroidal Thickness in Keratoconus Patients: Perspectives in the Disease Pathophysiology - João Pinheiro-Costa; João Viana Pinto; Sara Perestrelo; João Nuno Beato; Luís Torrão; Elisete Brandão; Ângela Carneiro; Maria Dulce Madeira; Fernando Falcão-Reis (Journal of Ophthalmology)
Purpose. To analyze and compare choroidal thickness between keratoconus (KC) patients and age-matched non-KC subjects. Methods. A cross-sectional, case-control study. One hundred and thirty-four keratoconic eyes and 78 control eyes, from individuals aged from 12 to 30 years old, were studied. Patients with KC followed in Corneal Department of Centro Hospitalar São João, Porto, Portugal, were identified and consecutively included between December 2017 and February 2018. A spectral-domain optical coherence tomography (OCT) using depth enhanced imaging was performed, and choroidal thickness in the center of the fovea and at 500 μm intervals along a horizontal section was measured and compared. Results. The statistical analysis showed that keratoconic eyes present a thicker choroid in every measured location (p<0.05). Mean subfoveal choroidal thickness (SFCT) values obtained were 375.86 ± 89.29 and 322.91 ± 85.14 in keratoconus and control groups, respectively (p<0.001). In a multivariate analysis, SFCT was significantly associated with spherical equivalent (p=0.004) and the presence of keratoconus (p<0.001), but not with age (p=0.167), gender (p=0.579), or best-corrected visual acuity (p=0.178). In a “fixed model,” keratoconus patients were found to have a 67.55 μm (95% CI 36.61–98.49) thicker subfoveal choroid compared to controls. Conclusion. Keratoconus patients seem to have a thicker choroid than healthy individuals. The exact pathophysiological mechanism resulting in a thicker choroid in KC patients is not known, but it could possibly be associated with inflammatory choroidal mechanisms.